The Control of the Tautomeric Equilibrium of Isocytosine by Intermolecular Interactions. Issue 37 (6th July 2018) - Pohl, Radek; Socha, Ondřej; Šála, Michal; Rejman, Dominik; Dračínský, Martin
Abstract : Isocytosine has two stable tautomers, which can form a dimer with each other, stabilised by three intermolecular hydrogen bonds similar to those in the guanine–cytosine base pair. Molecules with suitable donor/acceptor hydrogen‐bonding patterns can form intermolecular complexes with one or the other isocytosine tautomer. These intermolecular interactions stabilise the selected isocytosine tautomer, leading to an increase of its relative concentration. The integration of the 1 H NMR spectra acquired at various temperatures and concentrations was used for the determination of free‐energy changes of the formation of the isocytosine dimer/complex. The experimental free‐energy changes contain contributions from the formation of the isocytosine dimer/complex itself and from the rearrangement of the solvation shell. The latter contribution was estimated through a comparison of the experimental free‐energy changes with those calculated for the dimer/complex formation at the DFT level. The study demonstrates that the molecular environment can change relative tautomer stabilities, which supports the hypothesis of the involvement of rare nucleobase tautomers in the catalytic function of RNA enzymes. Abstract : Isocytosine tautomers can form a dimer with each other that are stabilised by three intermolecular hydrogen bonds. Molecules with suitable donor/acceptor hydrogen‐bonding patterns can form intermolecular complexes with one or the other isocytosine tautomer, leading to an increase of its relative concentration.